Globalization and Economic Regulation in China: Selective Adaptation of Globalized Norms and Practices - Pitman B. Potter (Washington University Global Studies Law Review, 2003)
This Article will examine changing norms and practices of economic regulation in China by reference to the dynamic of selective adaptation of norms of globalization.
Keywords: Commercial law; Economic policy; Globalization; China; International